Phenomenology of N,N-Dimethyltryptamine Use: A Thematic Analysis - COTT, CHRISTOPHER; ROCK, ADAM (Journal of Scientific Exploration, 2010)
N,N-dimethyltryptamine (DMT) is an endogenous hallucinogenic compound in the same chemical class as the more common psilocybin and the neurotransmitter serotonin. Despite previous experimental research assessing the subjective effects of DMT (e.g., Strassman et al., 1994), no qualitative studies have been conducted. Consequently, 19 DMT users were asked to provide thorough descriptions of the subjective effects of DMT via an online survey. A thematic analysis using various principles of phenomenological methodology elicited nine comprehensive constituent themes that ostensibly captured the essential aspects of the DMT-induced state. Keywords: N,N-dimethyltryptamine—phenomenology—thematic analysis